Generalized Banach Contraction Principles and Fixed Point Approximation - ช่อลำเจียก, ประสิทธิ์ (KKU Science Journal, 2012)
This article outlines a study of generalized Banach contraction principles and fixed point approximation for nonlinear mappings in complete metric spaces.